Health effects of night-shift work among manufacturing workers / Lim Yin Cheng - Lim, Yin Cheng (2019)
Occupational factors particularly night-shift work is attracting growing interest as a possible determinant of metabolic syndrome (MetS) and health-related quality of life (HRQoL). This thesis comprises two parts. The first part addressed study objectives 1 through 4; to determine the association between night-shift work and MetS, and between night-shift work and HRQoL, and further assess whether sleep quality was a mediating factor in these associations. The second part of the thesis addressed objective 5; to determine changes in the level of morning urinary 6-sulphatoxymelatonin after consecutive days of night-shift work, as a measure of circadian adaptation. To achieve objectives 1 to 4, a cross-sectional study was conducted among Malaysian manufacturing workers, aged 40-65 years old. Participants completed a selfadministered questionnaire on socio-demography, lifestyle, and family history, and the Pittsburgh Sleep Quality Index (PSQI) and HRQoL (Short Form-12 version 2 [SF12v2]) questionnaires. Waist circumference, blood pressure, fasting blood sugar, triglyceride and high-density lipoprotein levels were measured. Baron and Kenny’s method, Sobel’s test and multiple mediation model were used to determine whether PSQI global score or its components mediated the association between night-shift work and MetS, and between night-shift work and HRQoL. Of the 494 participants, 177 (36%) worked night shift and 51% were males. Prevalence of MetS was 37%. Nightshift work was found to be independently associated with a two-fold increase in risk of MetS (adjusted odds ratio: 1.92, 95% confidence interval: 1.24 to 2.97). However, the association between night-shift work and MetS did not appear to be modified by sex. Night-shift workers also reported significantly poorer sleep quality, longer sleep iv latency, shorter sleep duration, sleep disturbances, and daytime dysfunction. Robust mediation analysis nonetheless showed that neither PSQI global score nor its components mediated the association between night-shift work and MetS. On the other hand, Baron and Kenny’s method and Sobel’s test showed that PSQI global score was a significant mediator of the association between night-shift work and HRQoL. Bootstrapping showed a significant indirect effect of night-shift work through “subjective sleep quality” and “sleep disturbances” on physical health and through “sleep latency” and “daytime dysfunction” on mental health. To achieve objective 5, repeated measures of urinary 6-sulphatoxymelatonin on the morning before night-shift work and after first, third and fifth night-shift work was undertaken in 29 male, Malay, day-night-shift workers. The median age of participants was 29 years old. The highest level of urinary 6-sulphatoxymelatonin was at time point 1, followed by a significant reduction from time point 1 to time point 2, suggesting melatonin suppression due to light-at-night. Subsequently, there was a progressive increase of urinary 6- sulphatoxymelatonin from time point 2 to 4. This appears to suggest that workers were not able to achieve circadiam adaptation to night-shift work even after five days. In conclusion, early screening and management of MetS and the development of programmes to improve sleep quality should be carried out for night-shift workers. Findings from the second part of the study could be useful as a reference, in developing strategies to enhance circadian adaptation to night-shift work.